Verification of ERA5 reanalysis data for the interpretation of lidar investigation of high-level clouds - Penzin, Maxim S.; Bryukhanov, Ilia D.; Kuchinskaya, Olesya I.; Ni, Evgenii V.; Pustovalov, Konstantin N.; Zhivotenyuk, Ivan V.; Doroshkevich, Anton A.; Bordulev, Iurii S.; Samokhvalov, Ignatii V. 1943- (Proceedings of SPIE)
Interpretation of the data from lidar studies of high-level clouds requires information on the vertical profiles of meteorological quantities. The nearest aerological stations to Tomsk are located at about 250 km away from the city and launch radiosondes only twice a day. The ERA5 reanalysis was considered as a source of vertical profiles, which provides higher spatial and temporal resolution. It is compared with the aerological data, and the possibility of its using was evaluated in this research.